External quality assessment for one‐stage and chromogenic factor IX assays in samples containing Alprolix (rFIXFc) or Idelvion (rIX‐FP) and evidence that UK National External Quality Assessment Scheme for blood coagulation samples are commutable with patient samples. (17th January 2022) - Kitchen, Steve; Bowyer, Annette; Lowe, Anna; Jennings, Ian; Walker, Isobel D.
Abstract: Introduction: There may be clinically relevant differences between results of different FIX assays in samples containing extended half life FIX concentrates requiring regular surveillance of assay results through proficiency testing exercises. Control materials used in proficiency testing must be commutable, that is have the same inter‐assay properties as those demonstrated by authentic clinical samples when measured by different analytical methods. Methods: We assessed relationships between results with different FIX assays and commutability of UK National External Quality Assessment Scheme (NEQAS) materials containing rIX‐FP (Idelvion) or rFIXFc (Alprolix) by comparing results obtained using widely used one‐stage and chromogenic assays during a proficiency testing exercise with results obtained when analysing a series of individual patient samples using the same assay systems. NEQAS samples prepared by addition of either Idelvion or Alprolix to FIX deficient plasma were sent to 76 haemophilia centres in Europe. A total of 18 Idelvion and 22 Alprolix patient samples were assayed in a single centre. Two chromogenic and two one‐stage assays were compared. Results: The pattern of results obtained for NEQAS samples and patient samples was similar. In all cases, the NEQAS sample data point was within the scatter of patient sample data in plots of patient sample results showing one‐stage assay results using Synthasil or Actin FS plotted against chromogenic assay results with Biophen or Rox chromogenic FIX kits. Conclusion: This indicates that the NEQAS samples containing Idelvion or Alprolix were commutable and therefore suitable for use in proficiency testing exercises.